A freeze-and-thaw-induced fragment of the microtubule-associated protein tau in rat brain extracts: implications for the biochemical assessment of neurotoxicity. Issue 3 (26th March 2021) - Vasconcelos, Israel C.; Campos, Raquel M.; Schwaemmle, Hanna K.; Masson, Ana P.; Ferrari, Gustavo D.; Alberici, Luciane C.; Faça, Vitor M.; Garcia-Cairasco, Norberto; Sebollela, Adriano
Abstract: Tau is a microtubule-associated protein (MAP) responsible for controlling the stabilization of microtubules in neurons. Tau function is regulated by phosphorylation. However, in some neurological diseases Tau becomes aberrantly hyperphosphorylated, which contributes to the pathogenesis of neurological diseases, known as tauopathies. Western blotting (WB) has been widely employed to determine Tau levels in neurological disease models. However, Tau quantification by WB should be interpreted with care, as this approach has been recognized as prone to produce artifactual results if not properly performed. In the present study, our goal was to evaluate the influence of a freeze-and-thaw cycle, a common procedure preceding WB, to the integrity of Tau in brain homogenates from rats, 3xTg-AD mice and human samples. Homogenates were prepared in ice-cold RIPA buffer supplemented with protease/phosphatase inhibitors. Immediately after centrifugation, an aliquot of the extracts was analyzed via WB to quantify total and phosphorylated Tau levels. The remaining aliquots of the same extracts were stored for at least 2 weeks at either −20 or −80°C and then subjected to WB. Extracts from rodent brains submitted to freeze-and-thaw presented a ∼25 kDa fragment immunoreactive to anti-Tau antibodies. An in-gel digestion followed by mass spectrometry (MS) analysis in excised bands revealed this ∼25 kDa species corresponds to a Tau fragment. Freeze-and-thaw-induced Tau proteolysis was detected even when extracts were stored at −80°C. This phenomenon was not observed in human samples at any storage condition tested. Based on these findings, we strongly recommend the use of fresh extracts of brain samples in molecular analysis of Tau levels in rodents.